Oral dosage forms for drug delivery to the colon: an existing gap between research and commercial applications - Estefanía Martínez; Jennifer Gamboa; Carla V. Finkielstein; Ana Isabel Cañas; Marlon Andrés Osorio; Yesid Vélez; Néstor Llinas; Cristina Isabel Castro (Journal of Materials Science: Materials in Medicine)
Abstract Oral drug administration is the preferred route for pharmaceuticals, accounting for ~90% of the global pharmaceutical market due to its convenience and cost-effectiveness. This study provides a comprehensive scientific and technological analysis of the latest advances in oral dosage forms for colon-targeted drug delivery. Utilizing scientific and patent databases, along with a bibliometric analysis and bibliographical review, we compared the oral dosage forms (technology) with the specific application of the technology (colon delivery) using four search equations. Our findings reveal a gap in the publications and inventions associated with oral dosage forms for colon release compared to oral dosage forms for general applications. While tablets and capsules were found the most used dosage forms, other platforms such as nanoparticles, microparticles, and emulsions have been also explored. Enteric coatings are the most frequently applied excipient to prevent the early drug release in the stomach with pH-triggered systems being the predominant release mechanism. In summary, this review provides a comprehensive analysis of the last advancements and high-impact resources in the development of oral dosage forms for colon-targeted drug delivery, providing insights into the technological maturity of these approaches. Graphical Abstract